A MODEL FOR EVALUATING INFORMATION SECURITY SYSTEMS IN INDUSTRIAL ENTERPRISES AND ASSESSING ITS IMPACT ON INCREASING THE COMPETITIVENESS OF ENTERPRISES: A MODEL FOR EVALUATING INFORMATION SECURITY SYSTEMS IN INDUSTRIAL ENTERPRISES AND ASSESSING ITS IMPACT ON INCREASING THE COMPETITIVENESS OF ENTERPRISES - Kadieva, Zuhran; Dimitrova, Krasimira (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Globalization covers all spheres of life and economy in the modern world. The innovative development of information and communication technologies is a key factor in maintaining the competitiveness of companies on local, regional and global markets, which, however, is associated with certain risks. Information systems contribute to increasing the productivity of companies by catalyzing innovation and thus organizations gain an advantage over other players in their market. This process over the last few decades has established itself as a determining factor in the global market. The innovative development strategy of companies leads to competitive recovery, expansion and consolidation of market positions. In the fight against competitors, companies are looking for new solutions to optimize business, introducing intelligent information technologies in order to reduce the probability of making incorrect management decisions that would lead to adverse consequences.